PHYSICAL ACTIVITY AND HEALTH: THE BENEFITS OF PHYSICAL ACTIVITY IN THE PREVENTION OF DIABETES MELLITUS AND CARDIOVASCULAR DISORDERS - Ratko Pavlović; Sid Solaković; Simeonov, Aleksandar; Ljubo Milićević; Nikola Radulović (European Journal of Physical Education and Sport Science, 2022)
Public health of people and individuals is the most important resource in the modern world. The sugar epidemic and cardiovascular diseases are linked to the obesity epidemic. As obesity appears at younger and younger ages, it is to be expected that the proportion of people who have been obese for the number of years will increase and that those practicing a "sedentary lifestyle" will move less and less. Diabetes mellitus type 2 (DMT2) and cardiovascular diseases (CD) are among the top ten causes of death in the world. It is observed that the association between DMT2 and CD risk is not the same for both sexes, with the cardiovascular risk associated with DMT2 being greater in women. Among the different strategies for the prevention and treatment of DMT2 and risk factors for CD, physical exercise has been largely recommended because of its positive effects on glycemic control, body mass, blood pressure, and lipid profile. A higher level of daily physical activity significantly reduces the risk of contracting numerous diseases such as: diabetes, diseases of the heart and blood vessels, certain forms of malignant diseases, obesity, asthma, osteoporosis and others.
Keywords: diabetes mellitus, cardiovascular diseases, physical activity, benefits, prevention